Metacognitive Think-Aloud Strategy for Reading Comprehension in Vocational High Schools with Varying Student Anxiety Levels - Shinta Puspita Sari; Rudi Hartono; Suwandi Suwandi (Universitas Negeri Semarang, 2023)
Implementing effective strategy to teach reading comprehension is a must in order to overcome students’ obstacles in comprehending text. This study focuses on the effectiveness of Metacognitive Think a Loud Strategy in reading comprehension with different students’ anxiety. This study used quantitative research with a quasi experimental design. The data collection was done by using test and questionnaire to the students and conducted the pre-test and post-test. Then, to measure the data was analysed by using t-test in SPSS. The result of this study was that there was a significant effect of Metacognitive Think a Loud Strategy in teaching reading comprehension. There is a significant different between pre-test and post-test score of experimental class that using Meacognitive Think a Loud Strategy and there is significant different between experimental class and control class. Based on the data, it can be concluded that Metacognitive Think a Loud Strategy is effective in teaching reading comprehension with different students’ anxiety.